1999
DOI: 10.1002/(sici)1097-4644(19990601)73:3<303::aid-jcb2>3.3.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Complement‐derived anaphylatoxin C5a protects against glutamate‐mediated neurotoxicity

Abstract: Previous work from this laboratory indicates a role for the complement component C5 in neuroprotection against excitotoxicity. In the present study, we tested the hypothesis that the C5-derived anaphylatoxin C5a protects against kainic acid (KA)-induced neurodegeneration and investigated the mechanism of C5a neuronal activity in vitro. Brain intraventricular infusion of KA into adult mice caused neuronal morphological features of apoptosis in the pyramidal layer of the hippocampal formation as indicated by cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 0 publications
1
39
0
Order By: Relevance
“…Complement‐derived peptides C3a and C5a have been shown to provide a defence against neurotoxicity both in vivo and in vitro (Pasinetti et al. , 1996; Osaka et al. , 1999; van Beek et al.…”
Section: Discussionmentioning
confidence: 99%
“…Complement‐derived peptides C3a and C5a have been shown to provide a defence against neurotoxicity both in vivo and in vitro (Pasinetti et al. , 1996; Osaka et al. , 1999; van Beek et al.…”
Section: Discussionmentioning
confidence: 99%
“…Although we identified C5aR on primary cultured RPE cells and showed that C5a induces the generation of several cytokines in this report, there may be other roles that C5a has in the eye. In view of findings that neurons express C5aR [39,40] and a recent report [52] that C5a has a protective effect in glutamate‐mediated neurotoxicity in the brain, it is possible that in addition to being an inducer/regulator of inflammation, it may have a similar role on RPE cells or other C5aR + cells in the eye. Another recent report has shown that C5a is required for hepatocyte regeneration after toxic injury [53].…”
Section: Discussionmentioning
confidence: 99%
“…Both receptors are expressed on several CNS cell types, including microglia, astrocytes, oligodendrocytes, and neurons (Davoust et al, 1999; Nataf et al, 1999, 2001; O'Barr et al, 2001), but the effects of C3a and C5a in the CNS are not fully understood. C5a is neuroprotective against glutamate and β‐amyloid peptide‐mediated toxicity in vitro (Osaka et al, 1999; O'Barr et al, 2001), and C5‐deficient mice show increased neurodegeneration in response to intraventricular injection of kainic acid, another excitotoxin (Pasinetti et al, 1996). C3a has been reported to protect neurons against N‐methyl‐D‐aspartate‐induced toxicity (van Beek et al, 2001) and to induce production of the neutrophin nerve growth factor from human microglial cells in vitro (Heese et al, 1998).…”
mentioning
confidence: 99%